Exchange Rate Pass-through (ERPT) in Oil Producing Economy: Evidence from Nigeria - Deekor, Leelee (Advances in Social Sciences Research Journal, 2020)
This paper examines the pass-through of exchange rate to domestic prices in the context of oil producing economy. Essentially, the study utilizes an ARDL Bound cointegration test approach to determine the short-run and long-run dynamic of the pass-through. More so, it reflects the magnitude and the direction of the pass-through via Toda-Yamamoto VAR approach. The economic outcome of this study contributes to debate on the extent of pass-through of exchange rate and provides solution to intellectual puzzle on the impact of transmission of exchange rate movement to domestic prices in oil dependent economies